KAJIAN ANTROPOLOGI DALAM NOVEL HYOUKA KARYA YONEZAWA HONOBU - I Putu Agus Ambara Putra; A.A. Rai Laksmi; Ni Wayan Eminda Sari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2023)
This study aims to describe anthropological studies in the novel Hyouka by Yonezawa Honobu. In this study, several issues were raised, such as (1) How is the form of the anthropological elements of the language aspect in the novel Hyouka by Yonezawa Honobu, (2) How are the anthropological elements of the religious aspect in the novel Hyouka by Yonezawa Honobu, (3) How are the anthropological elements of the artistic aspect and culture in the novel Hyouka by Yonezawa Honobu, (4) How are the anthropological elements of the social system aspect in the novel Hyouka by Yonezawa Honobu. This study found several findings, namely, (1) Describing the anthropological elements of the language aspect in the novel Hyouka by Yonezawa Honobu, (2) Describing the anthropological elements of the religious aspect in the novel Hyouka by Yonezawa Honobu (3), Describing the anthropological elements of the artistic and cultural aspects in the novel Hyouka by Yonezawa Honobu (4), describes the anthropological elements of the social system aspect in the novel Hyouka by Yonezawa Honobu. This study uses a qualitative descriptive research method and in this research uses techniques of reading, noting, and describing the facts obtained then translated through analysis to obtain valid results. The research results obtained from the novel Hyouka are, (1) anthropological aspects of language such as speaking activities in interaction and the use of letters which are a type of written literature, (2) anthropology of religious aspects which contain a belief or magical power, (3) anthropology aspects of art and culture which are the result of human creativity which are used as a means of expressing desires, thoughts and understanding of nature - the environment, (4) anthropological aspects of social systems including systems that arise from human deficiencies needed to fill a certain space.